Postoperative Outcomes of Volar Plate Fixation in Cases of Scaphoid Deformity or Nonunion: A Case Series - Ansari, Saif A.; Kennedy, James A.; Younis, Fizan (Journal of Wrist Surgery, 2020)
Background Fractures through the waist of scaphoid are a common injury, resulting in deformity or nonunion. Recently, a locking plate has been shown to fix deformity or nonunion of scaphoid, with limited observation of functional postoperative outcomes.Objectives We present a case series of 16 patients, with the disabilities of the arm, shoulder, and hand (DASH) score evaluation in primary fixation of scaphoid fractures with humpback deformity (n = 11) and revision open reduction internal fixation (ORIF) for nonunion (n = 5), using the Medartis TriLock 1.5 scaphoid plate and bone grafting.Patients and Methods DASH scores were obtained preoperatively and postoperatively at 3, 6, and 12 (if required) months. Patient demographics, smoking status, employment type, and grip strengths were recorded.Results Thirteen patients attended follow-up. Union was clinically and radiologically assessed with 13 achieving union. The mean preoperative DASH score was 34.0 (n = 16) and at treatment completion (discharge or DNA) was 11.5 (n = 13), with mean reduction of 18.5 (p = 0.03). At treatment completion, mean reduction in DASH score of revision ORIF was 13.7 (p = 0.27; n = 4), compared with 20.7 (p < 0.01; n = 9) in primary fixation with plate.Conclusions Deformity correction, reduction in DASH score, and rate of union make the plate system useful in the management of scaphoid fractures with humpback deformity and revision for nonunion.Level of Evidence This is a Level IV study.
Keywords: scaphoid fracture; humpback deformity; nonunion; plate fixation; DASH score